Oral Presentations Abstracts: LEARNING PRACTICAL WISDOM FROM MORAL CASE DELIBERATION THROUGH MORISPRUDENCE - KOLE, Jos (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Moral case deliberation is regularly used as a teaching method at our medical school. Besides we facilitate moral case deliberation on the ward in our hospital. In both instances, our assumption is that practicing moral case deliberation will assist our (future) healthcare professionals to cultivate the virtue of practical wisdom. But, is this assumption, right? The answer to this question requires both empirical research and conceptual analysis. This paper focuses on the latter. The claim defended is that we can elucidate the relation between moral case deliberation and practical wisdom through an analysis of so called morisprudence. We start with discussing two divergent but related interpretations of morisprudence: one introduced by Toulmin and Jonsen, related to casuistry, and one related to a Dutch interpretation with a strong relation to moral case deliberation. The combination of the both interpretations shed new light on the conceptual connections between cultivating prudence (practical wisdom) and moral case deliberation, but it also provides new insights into the individual and collective dimensions of practical wisdom, of character formation within organizational contexts. Finally, it may have consequences for how moral case deliberation should actually be employed to teach practical wisdom.